Political power play, the law, and rural conflicts in Nigeria - Yikwab, Yikwabs Peter (Rural violence in contemporary Nigeria, 2023)
Clashes between farmers and herders in Nigeria have contributed to growing waves of rural violence in West Africa. This study analyses the Open Grazing and Ranches Establishment Law passed of 2017 in Benue state, Nigeria, as a microcosm of the significance of the political process – specifically power play – among elites in the fabrication or exacerbation of rural violence. This study draws on the integrated threat theory but suggests a need to grapple with the role of the political process in perceptions of threats. In particular, pre-existing widespread perceptions of threats led to enactment of an arguably non-inclusive law, which has worsened rather than attenuated communal violence. This supports the need to be cognizant of the discourses, policies, and laws favoured by various cadres of elites with differential allegiances and loyalties in the co-constitution of rural violence.